2022
DOI: 10.3390/s22155725
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Wireless Structural Health Monitoring of Bridges

Abstract: Nowadays, low-cost accelerometers are getting more attention from civil engineers to make Structural Health Monitoring (SHM) applications affordable and applicable to a broader range of structures. The present accelerometers based on Arduino or Raspberry Pi technologies in the literature share some of the following drawbacks: (1) high Noise Density (ND), (2) low sampling frequency, (3) not having the Internet’s timestamp with microsecond resolution, (4) not being used in experimental eigenfrequency analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…• Electrochemical sensors: the three main types of these sensors are (1) potentiometric sensors [219,220] (2) amperometric sensors [221,222] and (3) conductometric sensors [223,224]. • Wireless monitoring via wireless sensors: In recent decades, the development of wireless sensor technologies has been based on advancements in microelectromechanical systems (MEMS) technology, digital electronics, and wireless communications [225][226][227]. The two main subsystems of this system are (1) Portable Inspection and Maintenance Strategy (PIMS) [228,229] and (2) Portable Data Acquisition Strategy (PDAs) [230].…”
Section: Temperaturementioning
confidence: 99%
“…• Electrochemical sensors: the three main types of these sensors are (1) potentiometric sensors [219,220] (2) amperometric sensors [221,222] and (3) conductometric sensors [223,224]. • Wireless monitoring via wireless sensors: In recent decades, the development of wireless sensor technologies has been based on advancements in microelectromechanical systems (MEMS) technology, digital electronics, and wireless communications [225][226][227]. The two main subsystems of this system are (1) Portable Inspection and Maintenance Strategy (PIMS) [228,229] and (2) Portable Data Acquisition Strategy (PDAs) [230].…”
Section: Temperaturementioning
confidence: 99%
“…Low-cost sensor (LCS) usage for many aspects of structural health monitoring is evident in the literature due to the rapid advancement of micro sensor technology and microcontrollers (such as Arduino and Raspberry Pi) [ 39 , 40 ]. The monitoring of acceleration [ 41 , 42 , 43 ], tilt [ 44 ], temperature [ 45 , 46 ], humidity [ 47 ], and corrosion [ 19 ] are a few examples of this research. Komarizadehsasl et al [ 48 ] reported that, with a proper code and the right mode to exploit the features and potential of inexpensive electronics, it is possible to obtain valuable data that can provide useful insights for structural health monitoring applications.…”
Section: Introductionmentioning
confidence: 99%
“…A MEMS-based accelerometer with a wireless board was used as a sensor for measuring vibrations on a pedestrian deck-stiffened arch bridge, providing results very similar to those of experimental studies [ 7 ]. In another study, low-cost MEMS accelerometers with an Arduino module were utilized to address the noise density and synchronization problem and then used to remotely monitor the structural health of bridges [ 8 ]. Apart from vibration monitoring of machines discussed above, MEMS accelerometers are also used to monitor vibrations in automotives.…”
Section: Introductionmentioning
confidence: 99%